Personality types persistency, occupational consistency, and occupational satisfaction of graduates - Waruita, Ann Gathigia; Gitonga, Ciriaka Muriithi; Atitwa, Edwin Benson (International Journal of Evaluation and Research in Education (IJERE), 2025)
Personality type affects career path and can determine an individual’s job satisfaction or dissatisfaction after graduation. In Kenya, high graduate unemployment has forced many to seek jobs unrelated to their qualifications or personalities. The purpose of the current study was to examine persistency of Holland’s personality types, mediating effect of consistency of career choices, and the degree of occupational satisfaction, informed by Holland’s theory. Longitudinal cohort research design was adopted, to access participants involved in a study conducted in 2012, from which 76 participants were accessed and provided required data. Data was collected using Holland’s self-directed search 4th edition questionnaire and an interview schedule. Spearman’s rank correlation was used to determine correlation between persistency of personality types and occupational satisfaction. Logistic regression was used to check the mediating effects of consistency on the relationship between personality types and occupational satisfaction. Results of the study indicate that there was a positive significant relationship between persistency of personality types and occupational satisfaction at p<0.05; mediating effect of consistency on the relationship between personality types and occupational satisfaction was statistically significant at (β=0.254, p<0.05). This study highlights the importance of persistency of personality types and consistency of career choices in ensuring occupational satisfaction.